2019
DOI: 10.1111/ger.12397
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, oral health and nutrition in geriatrics inpatients: A cross‐sectional study

Abstract: Background Poor nutritional status is a risk factor for the development of frailty. Likewise, oral health is independently associated with nutrition. The potential association between oral health and frailty in hospitalised elderly adults has, however, not previously been investigated. Objective To investigate the relationship between oral health and frailty in hospitalised elderly adults and to identify the predictors of frailty. Method A cross‐sectional study of 168 geriatric inpatients >65 years old was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 27 publications
2
49
0
3
Order By: Relevance
“…Although none of the longitudinal studies that were evaluated in a review (5) indicated whether poor oral health increases the likelihood of developing signs of frailty, an association has been found between poor oral health (as loss of teeth) and frailty, and good oral hygiene is considered important to prevent the progression of frailty (32,33). In addition, self-reported oral health was found to have an independent negative association with frailty (31,34). Studies have also shown that frailty can proceed quite rapidly following the loss of teeth if Table 4 Associations between patient characteristics at baseline and ≥ twice-daily toothbrushing and denture cleaning from multivariate logistic regression, at baseline and after a 6-month follow-up (n = 231) people are physically and emotionally ill-prepared to manage the resultant stress (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although none of the longitudinal studies that were evaluated in a review (5) indicated whether poor oral health increases the likelihood of developing signs of frailty, an association has been found between poor oral health (as loss of teeth) and frailty, and good oral hygiene is considered important to prevent the progression of frailty (32,33). In addition, self-reported oral health was found to have an independent negative association with frailty (31,34). Studies have also shown that frailty can proceed quite rapidly following the loss of teeth if Table 4 Associations between patient characteristics at baseline and ≥ twice-daily toothbrushing and denture cleaning from multivariate logistic regression, at baseline and after a 6-month follow-up (n = 231) people are physically and emotionally ill-prepared to manage the resultant stress (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the sample in three different municipalities makes our study population more generally comparable to older people receiving home care in Finland. Most studies have focused on institutionalised or home‐dwelling older people and have hitherto mainly focused on only a few oral parameters (typically, presence or absence of teeth) in relation to individual aspects of being frail 31,50,51. The present study had no exclusion criteria regarding morbidity, age or cognitive status.…”
Section: Discussionmentioning
confidence: 99%
“…12 A deterioração da saúde bucal também é um agravante para doenças cardiovasculares e respiratórias infecciosas, endocardite, infecções articulares e, dentre outras, abscessos cerebrais. 1,11,13 A perda dentária é responsável por modificar a f isiologia normal, promove mudanças na aparência; redução da altura facial; protrusão do lábio inferior e do queixo; deficiências funcionais e sensoriais da mucosa oral e da musculatura; afeta a fala; a função mastigatória, 5,9,10,14 causando dor e desconforto; 15 abaixa a autoestima; sendo esses fatores contribuintes para uma autopercepção negativa da sua saúde oral. 9,11 A perda de dentes não é uma consequência normal do envelhecimento, mas sim uma culminação de eventos ao longo da v ida, 16 e isso limita a pa r t icipaç ão em ativ idades sociais, reduz a autoconf iança, causa um envelhecimento prematuro, altera a autoimagem, e reduz a socialização.…”
Section: Introductionunclassified
“…9,12 Uma dieta pouco saudável, 11 frequentemente monótona, com baixo teor de energia e deficiências de nutrientes, retinol, hidratos de carbono e ácido fólico 17 levam a deficiências funcionais, declínio da força muscular e fragilidade. 5,18 A autopercepção de saúde é considerada um bom indicador do estado de saúde, pois incorpora componentes físicos, cognitivos e emocionais. 3,19 Atualmente, os conceitos de saúde bucal são voltados a uma perspectiva psicossocial, a medidas qualitativas e à incorporação do ponto de vista do As questões que compõem o índice Gohai, bem como as respostas, estão descritas na sequência.…”
Section: Introductionunclassified
“…Çiğneme ve yutma ile ilgili problemler, protein ve lif, vitamin ve kalsiyum gibi zayıf besin ögelerinin alımıyla doğrudan ilişkiliyken, daha fazla yağ ve kolesterol alımını desteklemektedir. Bu nedenle, ağız sağlığı sorunlarının düzel-tilmesi besin alımını iyileştirebilir (38). Çok sayıda reçete edilen veya reçetesiz ilaçlar ağızda kuruluk ya da metalik tat, bulantı, kusma, kabızlık ve ishale neden olabilir.…”
unclassified